Gamma Irradiation-Induced Changes in Morphology, Nutritional Traits, and In Vitro Digestibility of Pennisetum purpureum cv. Mott on Post-Gold Mining Soil - Putra, B.; Karti, P. D. M. H.; Abdullah, L.; Prihantoro, I.; Wirnas, D.; Gopar, R. A. (Faculty of Animal Science, IPB University, 2026)
Post-mining lands, especially abandoned gold mining areas, present serious challenges for agriculture and forage cultivation due to poor soil fertility, heavy metal contamination, and damaged soil structure. To address these issues, this study evaluated the impact of gamma irradiation on the agronomic traits, nutritional content, anatomical characteristics, and in vitro digestibility of dry matter, organic matter, and fiber fractions of Pennisetum purpureum cv. Mott grown on degraded post-gold mining soil. A completely randomized design was used, applying seven doses of gamma rays (0, 5, 10, 15, 20, 25, and 30 Gy). Initially, irradiated plants were cultivated under optimal soil conditions. Selected cuttings were then transplanted onto post-mining soil for two months. Variables observed included growth performance, proximate composition, fiber fractions, macro minerals, and digestibility (dry matter digestibility [DMD], organic matter digestibility [OMD], in vitro digestibility [IVD], neutral detergent fiber digestibility [NDFD], acid detergent fiber digestibility [ADFD], cellulose digestibility [CeD], hemicellulose digestibility [HmD]). Results showed that a moderate dose of 10 Gy significantly enhanced dry matter digestibility, in vitro digestibility, and fiber degradation, accompanied by increases in crude protein and mineral levels. Anatomically, beneficial changes such as thicker mesophyll and vascular tissues were observed at this dose. While the 20 Gy dose also showed improvements in some fiber digestibility parameters, it did not provide an optimal balance with productivity, which was better achieved at 10 Gy. Multivariate analysis revealed distinct treatment clustering, reflecting physiological responses to irradiation. Cultivars treated with 10 Gy exhibited an optimal balance between productivity and forage quality. These findings suggest that gamma irradiation can successfully induce advantageous mutations, improving both adaptability and nutritional value of P. purpureum on marginal soils. In particular, a dose of 10 Gy is promising for breeding superior forage cultivars for the reclamation of post-mining land.